Synchronized Dual Pulse Gastric Electrical Stimulation Induces Activation of Enteric Glial Cells in Rats with Diabetic Gastroparesis. (10th April 2014) - Yang, Wei; Wang, Nian; Shi, Xue; Chen, Jie
Abstract : Objective. The aims of this study were to investigate the effects of synchronized dual pulse gastric electrical stimulation (SGES) on gastric motility in different periods for diabetic rats and try to explore the possible mechanisms of the effects. Methods. Forty-six rats were used in the study. Gastric slow waves were recorded at baseline, 7–14-day diabetes and 56–63-day diabetes before and after stimulation and the age-matched control groups. SGES-60 mins and SGES-7 days (60 mins/day) were performed to test the effects on gastric motility and to evaluate glial marker S100B expression in stomach. Results. (1) Gastric emptying was accelerated in 7–14-day diabetes and delayed in 56–63-day diabetes. (2) The S100B expression in 56–63-day diabetes decreased and the ultrastructure changed. (3) The age-associated loss of EGC was observed in 56–63-day control group. (4) SGES was able to not only accelerate gastric emptying but also normalize gastric slow waves. (5) The S100B expression increased after SGES and the ultrastructure of EGC was partially restored. The effect of SGES-7 days was superior to SGES-60 mins. Conclusions. Delayed gastric emptying due to the growth of age may be related to the EGC inactivation. The effects of the SGES on gastric motility may be associated with EGC activation.